2007
DOI: 10.1037/1541-1559.4.4.239
|View full text |Cite
|
Sign up to set email alerts
|

Women who served in Iraq seeking mental health services: Relationships between military sexual trauma, symptoms, and readjustment.

Abstract: Eighteen women who served in Operation Iraqi Freedom/Operation Enduring Freedom (OIF/OEF) sought mental health services at a Veterans' Affairs (VA) medical center. Ten of the 18 women (56%) reported military sexual trauma (MST) while serving in OIF/OEF. All 10 with MST reported sexual harassment, 6 of the 10 (33% of the sample) reported unwanted physical advances, and 3 (17%) reported completed assault or rape. Fifteen women also completed a questionnaire about their experiences and the Iraq Readjustment Inven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 19 publications
4
55
1
Order By: Relevance
“…It can be deduced from non-military-specific research that MST is likely to result in serious negative consequences. Sexual assault is one of the strongest predictors of posttraumatic distress among traumatic experiences (Kessler, Sonnega, Bromet, Hughes, & Nelson, 1995), including military-related traumas like combat (Fontana & Rosenheck, 1998;Katz, Bloor, Cojucar, & Draper, 2007;Wolfe et al, 1998). However, there is also evidence that MST is even more deleterious than civilian sexual trauma in that it has been associated with increased risk for PTSD relative to civilian sexual trauma Suris et al, 2004Suris et al, , 2007.…”
Section: Is Mst Comparable To Other Sexual Trauma?mentioning
confidence: 94%
“…It can be deduced from non-military-specific research that MST is likely to result in serious negative consequences. Sexual assault is one of the strongest predictors of posttraumatic distress among traumatic experiences (Kessler, Sonnega, Bromet, Hughes, & Nelson, 1995), including military-related traumas like combat (Fontana & Rosenheck, 1998;Katz, Bloor, Cojucar, & Draper, 2007;Wolfe et al, 1998). However, there is also evidence that MST is even more deleterious than civilian sexual trauma in that it has been associated with increased risk for PTSD relative to civilian sexual trauma Suris et al, 2004Suris et al, , 2007.…”
Section: Is Mst Comparable To Other Sexual Trauma?mentioning
confidence: 94%
“…The exception we found examined 15 female OIF veterans seeking mental health treatment and reported worse readjustment among the eight women with military sexual trauma histories compared to the seven women who did not have military sexual trauma histories (Katz, Bloor, Cojucar, & Draper, 2007). Researchers have examined constructs related to community reintegration (e.g., psychosocial or role functioning and quality of life), however, this was among veterans with psychiatric problems related to deployment.…”
mentioning
confidence: 92%
“…Recent research efforts have focused on the connection between stigma and mental disabilities in military contexts (e.g., Kim et al 2011, Witkiewitz andEstrada 2011). Interestingly, the few early studies attempting to link military disability and stigma were conducted in Israel, and demonstrated that attitudes toward physically disabled male veterans are more positive compared with other disabled groups, and they are less subjected to social stigmas, both by society and by themselves (Katz andShurka 1977, Kravetz et al 1994).…”
Section: Perceived Social Stigmamentioning
confidence: 96%
“…Katz et al (2007) discovered that the experiences of women during war are unique in comparison with men, and involve additional issues such as 'proving themselves', and dealing with harassment and sexual assault. These findings may also stem from the fact that the military roles of women have changed dramatically, from mainly nursing roles in the Vietnam War to participation in virtually every aspect of military activity, including combat roles (Bridges and Horsfall 2009).…”
Section: Military Disabilitymentioning
confidence: 98%